The factors influencing the usage of fixed line in the era of mobile phone in Taman Melawati / Soraya Zainal Abidin - Zainal Abidin, Soraya Zainal (Faculty of Business and Management, 2005)
Telekom is Malaysia's Number One provider of information communication technologies. The company vision is to be the world class telecommunications company providing total customer care. The company mission is to provide total customer satisfaction as they strive to become a world class telecommunications company. Telekom Malaysia is achieving this through developing people, products and services of the highest quality and meeting the needs of the nation, employees and shareholders.